2018
DOI: 10.2147/ott.s165840
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette–Guérin and anti-PD-L1 combination therapy boosts immune response against bladder cancer

Abstract: BackgroundProgrammed death-ligand 1 (PD-L1) is a critical immune checkpoint molecule which promotes immunosuppression by binding to PD-1 on T-cells in tumor immunity. We have previously identified that activation of toll like receptor 4 (TLR-4), which serves an important role in the induction of antitumor immune response during Bacillus Calmette–Guérin (BCG) immunotherapy, could upregulate PD-L1 expression in bladder cancer (BCa) cells through the classical mitogen-activated protein kinase (MAPK) pathway and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 26 publications
1
37
0
1
Order By: Relevance
“…Wang et al reported that treatment with a combination of BCG and anti-PD-L1 resulted in an enhanced anti-tumor effect in an orthotopic rat bladder cancer model by reducing tumor burden and prolonging survival. The antitumor immunity was attributed to an increase in the number and activity of tumor-infiltrating CD8+ T cells, as well as suppression of MDSCs in the TME (48).…”
Section: Combination Approaches: Personalized Immunomodulation Of a Pmentioning
confidence: 99%
“…Wang et al reported that treatment with a combination of BCG and anti-PD-L1 resulted in an enhanced anti-tumor effect in an orthotopic rat bladder cancer model by reducing tumor burden and prolonging survival. The antitumor immunity was attributed to an increase in the number and activity of tumor-infiltrating CD8+ T cells, as well as suppression of MDSCs in the TME (48).…”
Section: Combination Approaches: Personalized Immunomodulation Of a Pmentioning
confidence: 99%
“…17 These data suggest that the accumulation of PD-L1-expressing cells in bladder tissues could abrogate the effectiveness of BCG immunotherapy, a hypothesis reinforced by the recent finding that BCG and anti-PD-L1 combination therapy enhance the antitumor immunity in an animal model. 18 In addition to TILs, systemic immunological parameters have also been correlated with cancer outcome. The peripheral absolute lymphocyte count has been suggested to not only be a prognostic factor of survival in several tumor types 19 but also a predictor of treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, combinational therapy to boost immune responses by inducing cytosolic DNA with irradiation or inflammatory tumor death using a bacterial adjuvant (e.g. Bacillus Calmette–Guérin treatment) were proposed as possible strategies to improve the therapeutic efficacy of immunotherapy for UCUB . In UCUBs with YWHAZ amplification/overexpression, genes involved in interferon signaling, TLR‐4 signaling, inflammasome network, antigen presentation/TCR recognition, and CD28 co‐stimulation were found significantly downregulated (see supplementary material, Table S4).…”
Section: Discussionmentioning
confidence: 99%